Utilizing Children’s Song Videos To Create A Religious Character In Children With Intellectual Disabilities - Krisbiyanti, Billa; Utomo, Udi (Universitas Negeri Semarang, 2021)
Character education at SLB Negeri 1 Pemalang has not been able to run optimally since the emergence of the Covid-19 pandemic affecting the learning activities having to be carried out online. However, the efforts made by one of the teachers at SLB Negeri 1 Pemalang to create religious characters through song videos show that character education can still be done by utilizing technological advances in online learning. This study aims to describe and analyze children's song videos used by teachers to create religious characters for students with intellectual disabilities of class IV C at SLB Negeri 1 Pemalang. The research method of this study is descriptive qualitative. The results of this study show that the videos of songs by Nussa and Rara entitled